If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 + 15 = -4x + 11x Combine like terms: -29 + 15 = -14 -14 = -4x + 11x Combine like terms: -4x + 11x = 7x -14 = 7x Solving -14 = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -14 + -7x = 7x + -7x Combine like terms: 7x + -7x = 0 -14 + -7x = 0 Add '14' to each side of the equation. -14 + 14 + -7x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -7x = 0 + 14 -7x = 0 + 14 Combine like terms: 0 + 14 = 14 -7x = 14 Divide each side by '-7'. x = -2 Simplifying x = -2
| -4x-9x=-91 | | -8(-3)+2y=20 | | 10=5+4/5w | | l^2-5l=18 | | ln(x)-ln(7)=5 | | 9+5x/2=2x-4 | | 1/6b-1=12/3 | | 4x(x+y)= | | 65t=5t^2+12t | | y+3/5+y+22/3=9 | | -8=27-5f | | 10g+11=-19 | | -57/8n=-121/4 | | 2c+17=53 | | 8/9x=72 | | 6n(n+5)=66 | | -3/x-2+1-x/x | | 1/5m=-1 | | 6k-3k=12 | | 5(x+4)+2=2 | | 2x^2+4x-2.5=0 | | 200=6t^2+4.5t+74 | | 5(x+2)+2x=24 | | f(x)=(5x^2)-3 | | 2j^2-2j+3j-3=0 | | 6v^4w^4+8uv^2w=0 | | 20m^3+25m^2=0 | | -1.3x-9.4=0.4x+8.6 | | 3c^2+10c+3=0 | | ln(13)=ln(x+6)-ln(7) | | n=6t^2-4.5t+74 | | 126=(7+x)(12+x) |